Maharah Lugawiyah dalam Pembelajaran Daring Bahasa Arab - Majidatun Ahmala; Afidhotul Nur Azizah; Ayu Widya Ningsih (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
The purpose of learning Arabic language for students is to be able to use the Arabic language both orally and textually. Language proficiently (maharah lughawiyah) which is used as a measure of students ability in language is what teachers explore in teaching Arabic. Therefore, this study aims to determine how teachers can improve students’ Araic proficiently through online learning. This study used the descriptive qualitative method. Data collection techniques carried out in this study were observation, interviews, and documentation. The population of this study were all students of 5th grade students MI Ma’arif Pagerwojo from class A to class E, while the sampling technique used was simple random sampling with 94 students as respondents. The results of this study indicate that the four language’s proficienty at MI Ma’arif Pagerwojo are provided by the teacher by optimizing the whatsapp media as a communication tool between teachers and students and videos which used to optimize maharah istima’ as well as provide stimulus to students for optimize maharah kalam, qira’ah, and kitabah Keywords: Arabic language, language proficiency, maharah lughawiyah, online learning